Klugee: Web-Based Application for Teaching Mathematics in English to Indonesian Elementary School Students - Bebasari Amiroh (Ma Chung Press, 2021)
Despite the advancement of digital technology, there is no application specializing in teaching mathematics in English for Indonesian elementary school learners. During the pandemic, teachers need online teaching media to assist them when teaching mathematics. This article covers the project of teaching media creation for teaching Common Core mathematics to Indonesian elementary school students. The objectives of this project are creating web-based applications focusing to assist teachers to teach Mathematics in English for Indonesian Elementary students; and providing tools for the teachers in terms of material management such as curriculum and exercises; student management; and step-by-step guide during teaching in the classroom setting. Content and Language Integrated Learning (CLIL) is the teaching method supported by the teaching media. The results of the project are two web-based applications. The first application is the Learning Application which contains the mathematics teaching materials and student management. The second application is the Teaching Guide application, which contains the step-by-step-guide for teachers in CLIL classroom setting. The informal trials with 13 elementary students and 4 mathematics teachers as the participants showed positive results.